Comments on the KKM theory on hyperconvex metric spaces - Park, Sehie (Tamkang Journal of Mathematics, 2010)
Recent results in the KKM theory on abstract convex spaces and the related multimap classes KC and KO are applied to deduce generalizations of results on KKM maps in metric spaces in Amini et al. [1] and generalized KKM theorems on hyperconvex metric spaces in Chang et al. [4, 5].